Variasi Metode Dalam Pembelajaran Membaca di Program Studi Bahasa Jepang di Sekolah Vokasi UGM - Wahyu Handayani Setyaningsih (JLA (Jurnal Lingua Applicata), 2017)
Learning method is one of the important aspects to reach the aim of learning. In foreign language learning, especially in Japanese, various method is needed in order to improve the student’s skill and also give chance to the students to be more active in learning Japanese. This paper aims to explore the impact of various method used in Japanese learning in Vocational College, UGM. Based on the research, there are several impact on various method use to the student’s learning outcome. First, the students become more active in learning and show their opinions. Second, various method build the student’s self-reliance, and third, improving the student’s skill of communication, especially in Japanese.